The acute effect of passive and active stretching on hamstring flexibility and surface electromyography activity on students of International Islamic University Malaysia Kuantan Campus (IIUMK) - Norman, Siti Sarah; Mohamad, Mohd Yusof (IIUM Press, 2022)
Introduction:Stretching is known for its benefits in preventing sports injury due to hamstring tightness. This study aims to examine the effect of passive and active stretching on hamstring tightness by hamstring flexibility through active knee extension (AKE) and hamstring activation through surface electromyography (EMG) evaluation.Methods: Analyseson correlation of range of motion (ROM) through AKE and EMG were performed. 26 subjects were recruited following the inclusion and exclusion criteria. Results: The results demonstrated that both passive and active stretching with mean AKE measurement value of 9.63±10.37 and 9.26±7.17 degree respectively, improves hamstring flexibility, p<0.05. In contrast, in terms of muscle activation, there was no significance difference in passive and active stretching with mean EMG signal amplitude value of 7.19±242.03 MVIC and -5.73±208.45 respectively. The result of AKE and EMG reported no significant difference between passive and active stretching in terms of hamstring flexibility (p=0.611) and hamstring activation (p=0.259). There was no significant correlation between AKE and EMG either in passive (r=0.061) or active stretching (r=0.220). Conclusion: It is hoped that this study is able to bring useful insight on potential treatments for hamstring tightness in the future.